The Role of Language and Culture in Character Formation in Education - Hardini, Sri; Farhan, Arif; Zega, Irwansyah; Nainggolan, Gindo Tua; Purnama, Rizki Omilia; Harianto II (International Journal of Educational Research Excellence (IJERE), 2025)
This study explores the integral role of language and culture in shaping character within educational contexts. Language serves as both a medium of communication and a vehicle for cultural values and ethical principles, influencing how students perceive themselves and their interactions with others. By examining the interplay between language, culture, and character education, this study highlights the importance of a culturally responsive curriculum. Research indicates that integrating diverse linguistic and cultural perspectives in educational practices fosters empathy, respect, and social responsibility among students. Additionally, culturally relevant pedagogy encourages students to engage critically with their own values while appreciating the richness of others' backgrounds. Teacher training that emphasizes cultural competence is essential for creating inclusive learning environments, thereby enhancing character development. The findings suggest that educational systems must embrace linguistic and cultural diversity to effectively promote character education. By doing so, schools can cultivate well-rounded individuals who are not only academically proficient but also socially aware and ethically responsible. This article concludes by emphasizing the need for continuous research and practice in integrating language and culture into character formation, ensuring that education prepares students for the complexities of a globalized society.